The impact of professional seniority on the job satisfaction of nurses in the Saudi health sector - Al-Buraiki, Mohammed Ahmed; Al-Qahtani, Saud Ali; Al-Mutairi, Nayef Abdullah; Al-Ruwais, Abdullah Nawar; Shaghather, Muhammad Ali; Al-Anzi, Turki Sayah; Al-Shiha, Abdullah Saleh; Al-Anzi, Mona Obaid (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to identify the level of job satisfaction of nurses in the Saudi health sector, and the relationship between the effect of professional seniority on job satisfaction of nurses in the Saudi health sector. The government health sector in Saudi Arabia in the 2022 academic year. The total sample of the study was (346) individuals from the study population, and the study used the questionnaire to identify the objectives of the study. In light of the foregoing, the study reached a number of results, the most important of which is the presence of statistically significant differences at the level of 0.05, the average answers of the study community members about the degree of job satisfaction level of nurses in the Saudi health sector due to the variable of humiliating seniority, as it was found that the differences were in favor of their professional seniority from 11-15 years old. In light of the results, the study recommends conducting training courses and educational lectures for nurses in health institutions in the government sector by specialists in how to confront the professional psychological problems they face. and conducting more studies on the degree of job satisfaction on other work environments, "the private sector," a comparative study. As well as conducting more studies on the obstacles that contribute to raising the level of job satisfaction in the health environment and the ways, proposals and mechanisms that would enhance the level of job satisfaction among nurses in the Saudi health sector.
Keywords: Professional Seniority; Job Satisfaction; Nurses; Health Sector